The Temple Versus Jesus Christ As The Central Pointof Salvation: Hermeneutic Study Luke 23: 33-49 - Pai, Marva; Sendow, Mieke N. (International Journal of Education, Information Technology, and Others, 2025)
This paper aims to explain the interpretation of the Gospel of Luke 23: 33-49 by using a narrative approach to get the maximum interpretation and the right theology. Jesus died to save mankind and improve the relationship between man and God through the sacrifice of Jesus. The death of Jesus is no stranger in the Christian world, but the saving work of God through Jesus Christ is still a hot topic in the church. With the destruction of the temple, Jesus became the center of mankind. Thus, the work of God's salvation through Jesus Christ forms the basis of the faith of believers in Jesus and is the core of the story in the Gospels. It is hoped that this writing can give meaning to the narrative of Jesus Crucified and Jesus died and can apply it in everyday life